The Impact of Migration on Child Labor: Theory and Evidence from Brazil - Garance Genicot; Anna Maria Mayda; Mariapia Mendola (Institute of Labor Economics (IZA), 2016)
This paper investigates the impact of internal migration on child labor outcomes in Brazil. We develop a theoretical model and evaluate it on children aged 10 to 14 using two decades of Census data. In our model, migration impacts child labor through changes in the local labor market, which is made up of both adults and children. Thus we complement the individual-level child-labor analysis with an empirical study of the labor-market impact of internal migration within Brazil. We exploit variation in the concentration of both skilled and unskilled immigrants at the municipality level and employ an instrumental variable strategy that relies on the historical (1980) distribution of immigrants within the country. Our results show that internal migration of a given skill level has a negative impact on corresponding adults' labor market outcomes. We also find that unskilled (skilled) immigration has a negative (positive) and significant impact on child labor. Finally, unskilled immigration increases children school attendance and decreases their likelihood of being idle.
Keywords: F22; J61; O12; 330; child labor; migration